(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The routing protocol comprises of tiny sensing, processing and networking nodes. Recent developments have resulted in several modern routing protocols for sensor networks, in which energy understanding is an important architecture issue. The routing protocols have gained much interest as they may differ according to the device and network design. This paper then studies and compares the representatives of the routing protocols for wireless networks and presents their classification and contrast. The paper eventually suggests several potential future areas of study on wireless sensor network routing protocols.